(untitled) (Baghdad Science Journal, 2023)
This research includes a study of the ability of Iraqi porcelanite rocks powder to remove the basic Safranine dye from its aqueous process by adsorption. The experiments were carried out at 298Kelvin in order to determine the effect of the starting concentration for Safranin dye, mixing time, pH, and the effect of ionic Strength. The good conditions were perfect for safranine dye adsorption was performed when0.0200g from that adsorbed particles and the removal max percentage was found be 96.86% at 9 mg/L , 20 minutes adsorption time and at PH=8 and in 298 K. The isothermal equilibrum stoichiometric adsorption confirmed, the process data were examined by Langmuir, Freundlich and Temkin adsorption equations at different temperatures (298-338)K.The results of the adsorption were good suited for Freundlich and Langmuir Isotherm more than Temkin. Thermodynamic data found for adsorption processes ΔG0, ΔH0, ΔS0 indicates this is the removal step is through the adsorption operations which is spontaneity, exothermic and indicates a decrease in the randomness of that adsorbed dye molecules. Isotherms obtained from the experiments were identical to (S-curve) in form at Giles’ discretion.